Effect of standardized vs. local preoperative enteral feeding practice on the incidence of NEC in infants with duct dependent lesions: Protocol for a randomized control trial - Seliga-Siwecka, Joanna; Płotko, Ariel; Wójcik-Sep, Agata; Bokiniec, Renata; Latka-Grot, Julita; Żuk, Małgorzata; Furmańczyk, Konrad; Zieliński, Wojciech; Chrzanowska, Mariola (Frontiers in Cardiovascular Medicine, 2022)
Background Infants with duct dependent heart lesions often require invasive procedures during the neonatal or early infancy period. These patients remain a challenge for pediatric cardiologists, neonatologists, and intensive care unit personnel. A relevant portion of these infant suffer from respiratory, cardiac failure and may develop NEC, which leads to inadequate growth and nutrition, causing delayed or complicated cardiac surgery. Methods This randomized control trial will recruit term infants diagnosed with a duct dependant lesion within the first 72 h of life. After obtaining written parental consent patients will be randomized to either the physician led enteral feeding or protocol-based feeding group. The intervention will continue up to 28 days of life or day of cardiosurgical treatment, whichever comes first. The primary outcomes include NEC and death related to NEC. Secondary outcomes include among others, number of interrupted feedings, growth velocity, daily protein and caloric intake, days to reach full enteral feeding and on mechanical ventilation. Discussion Our study will be the first randomized control trial to evaluate if standard (as in healthy newborns) initiation and advancement of enteral feeding is safe, improves short term outcomes and does not increase the risk of NEC. If the studied feeding regime proves to be intact, swift implementation and advancement of enteral nutrition may become a recommendation. Trial registration The study protocol has been approved by the local ethical board. It is registered at ClinicalTrials.gov NCT05117164.